Fenomena Childfree Sebagai Budaya Masyarakat Kontemporer Indonesia Dari Perspektif Teori Feminis (Analisis Pengikut Media Sosial Childfree) - Ana Rita Dahnia; Anis Wahda Fadilla Adsana; Yohanna Meilani Putri (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2023)
Cultural society in the contemporary era, especially women, has many different perspectives on how to adapt to changing times. In the contemporary era, a woman has different currents of interests from pre-modern times, where the interests of women are now considered irrelevant to customs, which are mostly still upheld or embraced by the people of Indonesia, it is not uncommon for different opinions or mindsets to arise when they arise, causing criticism from people who are anti-feminine and who uphold customary principles. Contemporary women begin to get used to many taboos to form a new change or a new culture that is born by leaving the old culture regardless of religious teachings or customs, this experiment with new things has opened wide the minds of society, especially women, to get their rights. and choose their own path in life. This article discusses a new culture that was created in contemporary times that was born from the thoughts of women and young couples who thought of living without having children or being childfree, this phenomenon is currently rife among Indonesian society and has become a debate that reaps pros and cons, this article it is structured to unify the notion of thinking from the life choices of someone who chooses to be Childfree by combining a phenomenon with a sociological perspective, namely the theory of feminism. The theory of feminism is relevant to many problems that occur among women, this theory examines women in terms of psychology, identity, awareness, ethics, roles, positions, and the patriarchal system, this article opens the horizons of a woman to dare to hold opinions and choices his life.